Repairing Nanoparticle Surface Defects - Marino, Emanuele; Kodger, Thomas E.; Crisp, Ryan; Timmerman, Dolf; Macarthur, Katherine E.; Heggen, Marc; Schall, Peter (Angewandte Chemie International Edition, 2017)
Solar devices based on semiconductor nanoparticles require the use of conductive ligands; however, replacing the native, insulating ligands with conductive metal chalcogenide complexes introduces structural defects within the crystalline nanostructure that act as traps for charge carriers. We utilized atomically thin semiconductor nanoplatelets as a convenient platform for studying, both microscopically and spectroscopically, the development of defects during ligand exchange with the conductive ligands Na4SnS4 and (NH4)(4)Sn2S6. These defects can be repaired via mild chemical or thermal routes, through the addition of L-type ligands or wet annealing, respectively. This results in a higher-quality, conductive, colloidally stable nanomaterial that may be used as the active film in optoelectronic devices.
Keywords: ligand exchange; nanoplatelets; nanostructures; quantum dots; thiostannates